2001
DOI: 10.1034/j.1399-302x.2001.016005270.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary anticandidal activity and saliva composition in an HIV‐infected cohort

Abstract: This study investigated salivary anticandidal activity and salivary composition in stimulated whole saliva of 18 advanced HIV-infected patients and compared these values to healthy controls. Stimulated whole saliva from HIV-infected patients showed decreased anticandidal activity. The flow rate was reduced by 40% as compared with controls. The saliva flow rate for HIV-infected patients who had recoverable yeast in their saliva was reduced as compared to HIV-infected patients without recoverable yeast. For HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
47
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 34 publications
(58 reference statements)
9
47
0
4
Order By: Relevance
“…The prevalence of oral candidosis in HIV-positive patients appears to be correlated to the severity of immunological disfunction. 5,6 The occurrence of oral candidosis at initial stages of AIDS is common, particularly when the CD4 T cell count is low (400-700 cells/mm³). 5 The widespread use of antifungal agents to prevent the occurrence of oral candidosis in HIV-infected patients has been cited as an important factor for the positive selection of non-albicans species as opportunistic pathogens; these species have different susceptibilities to the antifungal agents utilized to treat C. albicans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of oral candidosis in HIV-positive patients appears to be correlated to the severity of immunological disfunction. 5,6 The occurrence of oral candidosis at initial stages of AIDS is common, particularly when the CD4 T cell count is low (400-700 cells/mm³). 5 The widespread use of antifungal agents to prevent the occurrence of oral candidosis in HIV-infected patients has been cited as an important factor for the positive selection of non-albicans species as opportunistic pathogens; these species have different susceptibilities to the antifungal agents utilized to treat C. albicans.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The occurrence of oral candidosis at initial stages of AIDS is common, particularly when the CD4 T cell count is low (400-700 cells/mm³). 5 The widespread use of antifungal agents to prevent the occurrence of oral candidosis in HIV-infected patients has been cited as an important factor for the positive selection of non-albicans species as opportunistic pathogens; these species have different susceptibilities to the antifungal agents utilized to treat C. albicans. 7 Certain non-albicans species, such as C. glabrata and C. krusei, are inherently less susceptible to fluconazole than C. albicans and have been isolated with increasing frequency in HIV-infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…10,11,12 The presence of oral candidiasis in HIV-infected and AIDS patients was associated with a number factors including low CD4 counts, increased viral load, xerostomia, age and Secretory aspartyl proteinase (Sap), extracellular hydrolytic enzyme was product by Candida. 7,10,13,14 Oral candidiasis occurs more frequently in HIVinfected patients with low CD4 counts. Imam et al found a statistically significant increase in the frequency of HIVrelated oral candidiaisis in patients with CD4 counts of less than 300 cells/mm 3 .…”
Section: Hiv/aids and Oral Candidiasismentioning
confidence: 99%
“…10,11 The prevalence ranges between 30 and 60% among HIV-infected subjects and reaches 90% in patients with AIDS. 12,13 Oral candidiasis in HIV-infected and AIDS patients may present as pseudomembranous, erythematous, hyperplastic and angular cheilitis variants. 10,11,12 The presence of oral candidiasis in HIV-infected and AIDS patients was associated with a number factors including low CD4 counts, increased viral load, xerostomia, age and Secretory aspartyl proteinase (Sap), extracellular hydrolytic enzyme was product by Candida.…”
Section: Hiv/aids and Oral Candidiasismentioning
confidence: 99%
See 1 more Smart Citation